How does European Integration affect the European Stock Markets? - Burcu Erdogan (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
This paper examines the integration of stock markets in Germany, France, Netherlands, Ireland and UK over January 1973-August 2008 at the aggregate market and industry level considering the following industries: basic materials, consumer goods, industrials, consumer services, health care and financials. The analysis is carried out by using correlation analysis, ß-convergence and s-convergence methods. ß-convergence serves to measure the speed of convergence and s-convergence serves to measure the degree of financial integration. It might be expected a priori that European stock markets have converged during the process of monetary, economic and financial integration in Europe. This study offers evidence for an increasing degree of integration both at the aggregate level and also at the industry level, although some differences in the speed and degree of convergence exist among stock markets. Surprisingly, there is an upswing of cross sectional dispersion for health care industry, which is more prone to regional shocks. The other industries show a significant s-convergence. The average half-life of a shock to convergence changes at a range from 5.75 days for aggregate market to 10.25 days for consumer goods.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C22; G12; G15; F36; 330; Financial integration; EU; stock markets; ß-convergence; s-convergence; correlation analysis; Europäische Wirtschafts- und Währungsunion; Aktienmarkt; Marktintegration; Kapitalmarktliberalisierung; Korrelation; EU-Staaten